PENERAPAN SANKSI ADMINISTRASI TERHADAP PELANGGARAN KETENTUAN PASAL 11 PERATURAN DAERAH KOTA PONTIANAK NOMOR 11 TAHUN 2019 TENTANG KETERTIBAN UMUM - MAULANA NIM. A1012161081 (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstracLocal governments as the authorities in the management of leaflets/ announcements/ advertising/pamphlets/posters, have a great responsibility in resolving management issues on leaflets/ announcements/ advertising/ pamphlets/ posters in their respective regions, both in terms of management strategies, management permits, and problems embedding in leaflets/ announcements/ advertising/ pamphlets/posters. In Law Number 11 of 2019 as a basis and guideline for leaflets/announcements/advertising/pamphlets/posters, it is emphasized that leaflets/announcements/ads/pamphlets/posters have become a national problem so that management needs to be carried out comprehensively and integrated from upstream to downstream. downstream in order to provide economic benefits, be healthy for the community, and safe for the environment, and can change people's behavior.In Law Number 11 of 2019 especially in Article 11 which says